1996
DOI: 10.1002/(sici)1096-9861(19960212)365:3<413::aid-cne6>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative analysis of glycine‐ and GABA‐immunoreactive nerve terminals on motoneuron cell bodies in the cat spinal cord: A postembedding electron microscopic study

Abstract: The distribution of glycine- and gamma-aminobutyric acid (GABA)-like immunoreactivity (LI) in nerve terminals on the cell soma of motoneurons in the aldehyde-fixed cat L7 spinal cord was examined using postembedding immunogold histochemistry in serial ultrathin sections. Quantitative examination of 405 terminals on eight neurons of alpha-motoneuron size in the L7 motor nuclei from one animal was performed. A majority of the terminals (69%) were immunoreactive to glycine and/or GABA. These terminals contained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 0 publications
7
36
0
Order By: Relevance
“…There is strong anatomical evidence for the colocalization of GABA A and glycine receptors at single postsynaptic densities (115, 1252, 1270) and for GABA and glycine colocalization in presynaptic terminals (937,941,942,1150,1205,1252). Electrophysiological measurements are consistent with GABAergic and glycinergic contributions to IPSP/C in cranial motoneurons (656), as well as recurrent (1099), afferent, and descending inhibitory inputs to spinal motoneurons (412,413,991,992,1191,1389).…”
Section: B) Colocalization/corelease Of Gaba and Glycinementioning
confidence: 86%
“…There is strong anatomical evidence for the colocalization of GABA A and glycine receptors at single postsynaptic densities (115, 1252, 1270) and for GABA and glycine colocalization in presynaptic terminals (937,941,942,1150,1205,1252). Electrophysiological measurements are consistent with GABAergic and glycinergic contributions to IPSP/C in cranial motoneurons (656), as well as recurrent (1099), afferent, and descending inhibitory inputs to spinal motoneurons (412,413,991,992,1191,1389).…”
Section: B) Colocalization/corelease Of Gaba and Glycinementioning
confidence: 86%
“…Early protocols for post-embedding immuno-gold studies allowed for the detection of amino acid transmitters, including glutamate, GABA, and glycine in the brain and spinal cord (Ottersen, 1987; Örnung, 1996, 1998). Alternatively, freeze-substitution and embedding of fixed brain tissue in Lowicryl HM20 has demonstrated excellent antigen preservation and suitability for immunogold localization of neural antigens in the electron microscope (van Lookeren Campagne et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Studies using intracellular recording in rodent in vitro preparation showed that glycine and GABA are either colocalized and coreleased from the same presynaptic vesicle or released from the separate terminals onto spinal and cranial motoneurons (Jonas et al, 1998;O'Brien and Berger, 1999;Russier et al, 2002). Anatomical studies also demonstrated that input terminals on spinal motoneurons contain GABA, glycine, or both (Taal and Holstege, 1994;Ornung et al, 1996). The present study suggests that both glycine and GABA release contribute to the active inhibition of muscle tone during electrical stimulation and after ACh stimulation of PIA, as well as during the normal release of ACh on the PIA in REM sleep (Kodama et al, 1990).…”
Section: Discussionmentioning
confidence: 99%